2012
DOI: 10.2131/jts.37.139
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of sulphoraphane against oxidative stress mediated toxicity induced by CuO nanoparticles in mouse embryonic fibroblasts BALB 3T3

Abstract: -Despite the great interest in nanoparticles (NPs) safety, no comprehensive test paradigm has been developed. Oxidative stress has been implicated as an explanation behind the toxicity of NPs. It is reported that sulphoraphane (SFN) present in cruciferous vegetables like cauliflower and broccoli has potential to protect cells from oxidative damage and inflammation. However, protective role of SFN in nanotoxicity is not explored. We investigated the protective effect of SFN against the toxic response of copper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 52 publications
1
23
0
Order By: Relevance
“…These cell lines have been extensively utilized in toxicity studies. [16][17][18][19] To explore the underlying molecular mechanisms of apoptosis induced by ZnO NPs, we have further utilized the human liver cancer HepG2 cells. Quantitative real-time polymerase chain reaction (PCR) and Western blotting techniques were used to determine both the mRNA and protein levels of p53, bax, bcl-2, and caspase-3 genes involved in apoptotic pathways.…”
Section: Introductionmentioning
confidence: 99%
“…These cell lines have been extensively utilized in toxicity studies. [16][17][18][19] To explore the underlying molecular mechanisms of apoptosis induced by ZnO NPs, we have further utilized the human liver cancer HepG2 cells. Quantitative real-time polymerase chain reaction (PCR) and Western blotting techniques were used to determine both the mRNA and protein levels of p53, bax, bcl-2, and caspase-3 genes involved in apoptotic pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies reported that CuONP induced reactive oxygen species (ROS) generation in different cells, 10,13,18,32 including keratinocytes 16 and fibroblasts. 33 For example, Alarifi et al reported that CuONP induced dosedependent cell death and ROS generation in keratinocytes. 16 Considering that ROS generation would activate Erk, 29,34,35 the dose-dependent Erk activation in the present work might be similarly due to CuONP-induced ROS generation.…”
mentioning
confidence: 99%
“…The viability of SH-SY5Y cells was determined using MTT assay to test the Ab 1e40 peptides (Akhtar et al, 2012) or lactate dehydrogenase (LDH) release assay to test the Ab 1e42 peptides (Sigma, St-Louis, MO, USA). In the 2 series of experiments, 6 Â 10 4 SH-SY5Y cells/well were seeded in 96-well plates and repeatedly treated or not with GHB 1 mM in the presence or absence of thiorphan 50 mM during 2 days.…”
Section: Cell Viability and Cytotoxicitymentioning
confidence: 99%